An efficient computational model for unequal-area dynamic facility layout problems considering input/output locations under algorithms case - Seyedi, Seyed Bardia; Attari, Mahdi Yousefi Nejad; Ghadim, Vahid Abbasgholi Pour; Ala, Ali (Sadhana (Bangalore), 2024)
Recently, the adaptability of production systems is crucial for various facilities or departments, focusing on minimizing the cost associated with material flow in facility layout problems. To address these challenges, an examination of dynamic problems becomes imperative. This paper presents a mathematical model designed explicitly for dynamic facility layout problems (DFLP) characterized by fixed shapes and unequal areas. The model incorporates input and output points, allowing flexibility in their placement within facilities, and treats material handling system input/output (I/O) points as decision variables. The proposed approach utilizes an Improved Particle Swarm Optimization algorithm (IPSO) and an Improved Genetic Algorithm (IGA) to solve the resulting mixed integer nonlinear programming (MINLP) model. Both a theoretical problem and a real-world case are employed to assess the effectiveness of the suggested algorithms. The outcomes demonstrate that the proposed algorithm outperforms the compared algorithms in identifying optimal solutions.